Early post-transplant neopterin associated with one year survival and bacteremia in liver transplant recipients - Oweira, Hani; Lahdou, Imad; Daniel, Volker; Hofer, Stefan; Mieth, Markus; Schmidt, Jan; Schemmer, Peter; Opelz, Gerhard; Mehrabi, Arianeb; Sadeghi, Mahmoud (Human immunology, 2016)
Bacterial infections are the most common complications, and the major cause of mortality after liver transplantation (Tx). Neopterin, a marker of immune activation, is produced in monocyte/macrophages in response to inflammation. The aim of our study was to investigate whether early post-operation serum levels of neopterin were associated with post-transplant bacteremia and mortality in liver transplant recipients. We studied 162 of 262 liver Tx patients between January 2008 and February 2011 of whom pre- and early post-Tx sera samples were available. Pre- and early post-operative risk factors of infection and mortality were evaluated in 45 bacteremic patients and 117 non-bacteremic patients. During one-year follow-up, 28 of 262 patients died because of graft failure, septicemia and other diseases. Post-Tx serum neopterin on day 10 (p<0.001) were significantly higher in bacteriemic patients than in patients without bacteremia. Logistic regression analyses showed that day 10 post-Tx neopterin serum level ⩾40nmol/l has a predictive value (OR=6.86: p<0.001) for bacteremia and mortality (OR=3.47: p=0.021). Our results suggest that early post-Tx neopterin serum levels are very sensitive predictive markers of one-year post-Tx bacteremia and mortality in liver Tx recipients.
Published online 12 November 2015
Gesehen am 26.06.2020